Interplay of individual and food environment factors shaping diets in the Kisumu urban informal settlements - Musita, Consolata Nolega; Ngala, Sophia; Abong, George; Akingbemisilu, Tosin Harold; Termote, Celine (FRONTIERS MEDIA, 2025)
Introduction Malnutrition persists in Kenyan urban informal settlements, disproportionately affecting women and children. This study explores the complex interplay between individual-level and food environment factors and the on influence dietary outcomes for women and children in these settings.